Adherence to antiretroviral therapy among HIV patients at a hospital in Tacna, Peru - Brayan Miranda-Chavez; Monica Mejia-Copaja; Alvaro Taype-Rondan (Clinical Epidemiology and Global Health)
Objective: This study aims to provide an overview of antiretroviral therapy adherence and its related factors within a hospital in southern Peru. Materials and methods: We conducted an analytical cross-sectional study spanning from April to October 2022. This study involved a review of medical records and the administration of a survey to individuals living with Human Immunodeficiency Virus. Adherence to antiretroviral treatment was assessed using the CEAT-HIV (Questionnaire for the Evaluation of Antiretroviral Treatment Adherence), and was categorized as high, adequate, insufficient, or low. The statistical analysis included the calculation of crude and adjusted prevalence ratios (PRs). Results: Our study comprised 300 participants, with a median age of 30 years, predominantly male (78.3 %). Among these individuals, 83 % exhibited low or insufficient adherence to antiretroviral treatment according to the CEAT-VIH scale. Notably, patients with a viral load >50,000 copies/ml scored higher on the CEAT-VIH scale than those with a viral load <400 (adjusted PR: 2.78, 95 % CI: 1.21 to 6.40). Furthermore, a higher level of education and a viral load below 400 copies/ml were associated to higher scores in the treatment compliance dimension of the CEAT-VIH scale. Conclusion: Eight out of ten evaluated patients exhibited low or insufficient adherence. While lower adherence was correlated with lower education, the connection between viral load and adherence remains inconclusive.